Structural, spectroscopic, and photochemical study of ethyl propiolate isolated in cryogenic argon and nitrogen matrices - Lopes, S. (2020)
Ethyl propiolate (HC ≡ CCOOCH2CH3, EP) was studied experimentally by infrared spectroscopy in argon and nitrogen cryomatrices (15 K) and by quantum chemical calculations (at the DFT(B3LYP) and MP2 levels of theory). Calculations predict the existence of four conformers: two low-energy conformers (I and II) possessing the carboxylic moiety in the cis configuration (O=C-O-C dihedral equal to ~0°) and two higher-energy trans forms (O=C-O-C dihedral equal to ~180°; III and IV). The conformation of the ethyl ester group within each pair of conformers is either anti (C-O-C-C equal to 180°; in conformers I and III) or gauche (C-O-C-C equal to ±86.6° in II, and ± 92.5° in IV). The two low-energy cis conformers (I and II) were predicted to differ in energy by less than 2.5 kJ mol-1 and were shown to be present in the studied cryogenic matrices. Characteristic bands for each one of these conformers were identified in the infrared spectra of the matrix-isolated compound and assigned taking into account the results of normal coordinate analysis, which used the geometries and harmonic force constants obtained in the DFT calculations. The two trans conformers (III and IV) were estimated to be 17.5 kJ mol-1 higher in energy than the conformational ground state (form I) and were not observed experimentally. The unimolecular photochemistry of matrix-isolated EP (in N2 matrix) was also investigated. In situ irradiation with UV light (λ > 235 nm) leads mainly to decarbonylation of the compound, with generation of ethoxyethyne, which in a subsequent photoreaction generates ketene (plus ethene).